1997
DOI: 10.1128/cdli.4.3.387-391.1997
|View full text |Cite
|
Sign up to set email alerts
|

Microplate hybridization for Borna disease virus RNA in human peripheral blood mononuclear cells

Abstract: We developed a simple and sensitive microplate hybridization procedure with which to identify Borna disease virus cDNA in amplified products from human peripheral blood mononuclear cells. The mean values for the positive PCR products were significant compared with those for any of the negative products, indicating that this method can be applied to rapidly diagnose a large number of clinical specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…malignant brain tumors of patients p24, p25, p30, p31 and p18, respectively, of Nakaya et al [34] demonstrate close relationship to strain He/80, thus indicating the source of contamination in this study. The partial sequences from psychiatric patients reported by Fujiwara et al [35] are either related to strain He/80 (lanes 1 þ 2) or to strain H1766 (lane 3), whereas the reported amplified pseudo-p24 fragments are identical to parts of the human genome (see GenBank acc. no.…”
Section: Sequence Analyses Of the Tü Bingen Sequence Group Consistingmentioning
confidence: 99%
See 1 more Smart Citation
“…malignant brain tumors of patients p24, p25, p30, p31 and p18, respectively, of Nakaya et al [34] demonstrate close relationship to strain He/80, thus indicating the source of contamination in this study. The partial sequences from psychiatric patients reported by Fujiwara et al [35] are either related to strain He/80 (lanes 1 þ 2) or to strain H1766 (lane 3), whereas the reported amplified pseudo-p24 fragments are identical to parts of the human genome (see GenBank acc. no.…”
Section: Sequence Analyses Of the Tü Bingen Sequence Group Consistingmentioning
confidence: 99%
“…These sequences as well as the many other reports of successful BDV RT-PCR amplifications in human samples without sequencing cannot be evaluated. Independent of the issue of contamination that cannot be investigated for such reports, it even cannot be concluded that all of these PCR products are indeed BDV amplification products especially since Fujiwara et al [35] described the successful amplification of unspecific pseudofragments from the human genome by employing p24 BDV primers in some of the samples they investigated (see above).…”
Section: Sequence Analyses Of the Brazil Sequence Group Consisting Ofmentioning
confidence: 99%
“…In this procedure, hybridization of the detection probe was performed without the addition of formamide, which is commonly used for identification of microbes using oligo-FISH for 16 S rRNA 19,20 . The procedure without addition of formamide is often used to verify the sequence of PCR products by Southern hybridization [21][22][23] . If it is not crucial to detect the exact same sequence, especially when using artificial sequences, it is unnecessary to add formamide for hybridization under high-stringency conditions.…”
Section: Resultsmentioning
confidence: 99%